Peace and Inter-Faith Dialogue: An Islamic Approach in the Indian Context - Yoginder Singh Sikand (حقوق بشر)
India is home to a remarkable variety of religions, and a major challenge that the country faces today is that of conflict between various religious communities. This has taken on menacing forms in recent decades. Incidents of violence between Hindus and Muslims, in which often agencies of the state play a central role in directing anti-Muslim violence, have now become endemic in some parts of the country. This form of communal violence, generally instigated by right-wing Hindu forces, is sought to be given religious sanction and is also projected as a crusade to save the Indian “nation”, which is described and portrayed in Hindu terms. Communal violence and anti-Muslim pogroms in various parts of the country have resulted in mounting human rights violations, particularly of marginalised communities such as the country’s Muslims, who number more than 150 million.